Lesni odpadki in biomasa - Nagode, Matej (Gozdarski vestnik, 2025)
n Slovenia, wood waste and biomass play a major role in the circular economy and sustainable use of resources. Wood waste is all parts of a tree or already processed wood waste that is discarded as unusable by the holders in a certain process and most often originates from the wood processing industry. In Slovenia, the amount of wood waste is decreasing due to its use for energy purposes and inventive reuse in woodworking plants, while the amount of non-wood waste is increasing. Legislation sets the conditions for when waste ceases to be waste and becomes a raw material, which enables sustainable use and promotes the circulation of raw materials. However, the definition of waste and the change of status are left to the processing and treatment process itself. The purpose of the circular economy with wood waste is thus to promote reuse and recycling and reduce the impact on the environment. At the same time, the forestry and woodworking professions are trying to find ways to make processing and collection even more efficient.
Keywords: biomasa; biomass; legislation; lesni odpadki; wood waste; zakonodaja